Acute intense fatigue does not modify the effect of EVA and TPU custom foot orthoses on running mechanics, running economy and perceived comfort - Van Alsenoy, K.; Ryu, J. H.; Girard, O. (European Journal of Applied Physiology, 2022)
We determined whether fatigue modifies the effect of custom foot orthoses manufactured from ethyl-vinyl acetate (EVA) and expanded thermoplastic polyurethane (TPU) materials, both compared to standardized footwear (CON), on running mechanics, running economy, and perceived comfort. Eighteen well-trained, males ran on an instrumented treadmill for 6 min at the speed corresponding to their first ventilatory threshold (13.8 ± 1.1 km/h) in three footwear conditions (CON, EVA, and TPU). Immediately after completion of a repeated-sprints exercise (8 × 5 s treadmill sprints, rest = 25 s), these run tests were replicated. Running mechanics, running economy and perceived comfort were determined. Two-way repeated measures ANOVA [condition (CON, EVA, and TPU) × fatigue (fresh and fatigued)] were conducted. Flight time shortened (P = 0.026), peak braking (P = 0.016) and push-off (P = 0.032) forces decreased and vertical stiffness increased (P = 0.014) from before to after the repeated-sprint exercise, independent of footwear condition. There was a global fatigue-induced deterioration in running economy (- 1.6 ± 0.4%; P < 0.001). There was no significant condition × fatigue [except mean loading rate (P = 0.046)] for the large majority of biomechanical, cardio-respiratory [except minute ventilation (P = 0.020) and breathing frequency (P = 0.019)] and perceived comfort variables. Acute intense fatigue does not modify the effect of custom foot orthoses with different resilience characteristics on running mechanics, running economy and perceived comfort.